T. S. MILLER – J. W. NESBITT, Walking Corpses: Leprosy in Byzantium and the Medieval West, Ithaca; London: Cornell University Press, 2014. Pp. xiv, 243. ISBN 9780801451355 - LAZARIS, Stavros (Byzantina Symmeikta, 2016)
T. S. Miller – J. W. Nesbitt, Walking Corpses: Leprosy in Byzantium and the Medieval West, Ithaca; London: Cornell University Press, 2014. Pp. xiv, 243. ISBN 9780801451355